Literature - A Fountainhead Of Values For A Better Society (Journal of Namibian Studies : History Politics Culture, 2023)
A value based education plays a vital and pivotal role in the upliftment of the society making it the best and a blessed place to live in. The values and morals that literature cultivates and advocates help the society become morally strong, ethically undaunted and psychologically stable and secure. Literature imparts values through various literary works by citing examples with the help of stories, novels, poems, essays and epistles. In this article we tried enumerating all these.